Steiner's cephalometric analysis of Filipino students aged 16-25 - Lim, Jerralynne V.
This paper is a study of Steiner's Cephalometric Analysis of University Students in Manila Aged 16-25 years old. 34 students from 3 different Universities who fit the criteria set were utilized as subjects for this study. The purpose of this investigation was to determine the normal Cephalometric values of university students in Manila and compare them with values of other ethnic groups particularly the Caucasians, Hawaiians, Japanese, Chinese and Negroes. This was also compared with the normal cephalometric values obtained by previous researchers using Filipino subjects particularly that of Sabater and Quejada. Results showed that Filipinos basically present a Class I skeletal profile coupled with a bimaxillary protrusion of the upper and lower denture pattern. Filipinos have a fuller mouth profile, this is not of skeletal in origin but rather is due to the axial inclination of the upper and lower incisors. Results of this study also showed the importance of individuality of treatment plan particularly those involving different ethnic groups.